Numerical methods with worked examples: Matlab edition - Woodford, C. (Springer Netherlands, 2012)
This book is for students following an introductory course in numerical methods, numerical techniques or numerical analysis. It introduces MATLAB as a computing environment for experimenting with numerical methods. It approaches the subject from a pragmatic viewpoint; theory is kept at a minimum commensurate with comprehensive coverage of the subject and it contains abundant worked examples which provide easy understanding through a clear and concise theoretical treatment. This edition places even greater emphasis on 'learning by doing' than the previous edition.   Fully documented MATLAB code for the numerical methods described in the book will be available as supplementary material to to the book on http://extras.springer.com